Pengembangan Usaha Ekonomi Produktif pada Dasawisma 2 RT 01 RW 11 Desa Makamhaji Kecamatan Kartosuro Kabupaten Sukoharjo - Setyowati Setyowati; Wiwit Rahayu (PRIMA: Journal of Community Empowering and Services, 2020)
Title: Development of Productive Economic Business in Dasawisma 2 RT 01 RW 11 Makamhaji Village, Kartosuro District, Sukoharjo RegencyDasawisma has the potential to improve family welfare through the productive efforts of dasawisma members. Some members of dasawisma 2 Gobayan RT 01 RW XI Makamhaji Village have skills in making food preparations but have not yet developed. The problems faced were a lack of understanding of entrepreneurship and the limitations of production equipment. This community service is done to overcome this problem. Activities undertaken include entrepreneurship training, introduction of production equipment (stick-making equipment, scales, and sealers), and mentoring. The results of this community service activity were members of dasawisma have knowledge about entrepreneurship, they were motivated to become entrepreneurs, and have production tools that can be used to make stick businesses. The results of monitoring and evaluation showed that members of dasawisma had made various flavor sticks and were then sold to stalls, sold online, and also received orders. These community service activities have led to productive economic bussines that are beneficial to increase the household income of the dasa wisma members